Design, construction and use of an apparatus for the measurement of normal total emissivity of surfaces of opaque materials at ordinary temperatures - Mehmetoğlu, Halil. (Thesis (M.S.) - Robert College. Faculty of Graduate School of Engineering, 1969., 1969)
Faotors effecting the emissivity of surfaces are discussed. A standard apparatus for .the measurement of emissivity is described. The design fea.tures of the apparatus used we explained; and tests on several paints, tarred paper, asbestos paper, aluminum foil and copper, nickel and. aluminum sheets are reported. The tests conducted indicated that the performance of the apparatus was satisfactory exoept for very low emissivity surfaces.
Keywords: Emissivity.; Heat -- Radiation and absorption.; Heat -- Transmission.